Effects Of Different Gelling Agents And Puree Content In The Preparation Of Red Pitaya Fruits (Hylocereus Polyrhizus) Gummy Candy - Romli, Siti Rashima (2015)
Gummy fruit candy based on red pitaya fruit iHylocerens polyrhizusi was developed using high-methoxyl pectin (HMP) and fish gelatin (FG) as gelling agents. Different types of gummy candy were prepared based on various formulations using two concentrations (20 and 25 %, w/w) of red pitaya puree (RPP) and different gelling agent to water ratios (pectin/water